Alpenverein Die Städter entdecken die Alpen - Gidl, Anneliese (2007)
The Deutsche und Österreichische Alpenverein resulted from a merger of the Österreichischer Alpenverein founded in 1862 with the Deutsche Alpenverein in 1873. Both clubs had been initiated by urban circles in Vienna, Munich and other major cities in Germany and Austria. The Alpenverei soon became very popular and on the eve of World War I had more than 100.000 members. In the beginning, the Alpenverein concentrated its activities on the scientific exploration of the Alps, which was regularly reported upon in its periodicals. Subsequently, the Alpenverein established a regular service of well educated mountain guides as well as a net of thousands of kilometres of mountain routes and mountain huts to serve the needs of the growing number of Alpine tourists. Routes and huts were established by the numerous sections founded over the decades between the North Sea in the north and the Adriatic Sea in the south, between Strassbourg in the west and Königsberg in the east. Besides such practical goals, the Alpenverein also cherished ideal motives such as the intention of providing city dwellers by way of compensation with the chance of enjoying nature and finding physical recreation, which at the same were to foster qualities of character such as determination, daring and presence of mind. The sections - besides giving information on the Alps - also cherished the social life among their members, especially during the annual general meetings, which were organized alternately by various sections and which were to rank among the highlights of urban social life. The exploration and visits of the Alps were often related with a kind of colonial though well intended attempts to influence the alpine population, since the Alpenverein also considered itself a "provider of culture". The alpine population, however, had - at least in the beginning and with but few exceptions - only little understanding for the activities of the alpine tourists, although in the end and as a consequence of the emerging alpine tourism, which was strongly promoted by the Alpenverein, the benefits prevailed. After many years of peaceful development characterized by cooperation not only between the German and the Austrian sections of the club, but also between the Alpenverein and similar clubs in the neighbouring alpine countries, the political conflicts before and during World War I resulted in more radical attitudes within the Alpenverein, especially vis-a-vis the Italian side. Thanks to its knowledge and infrastructure in the Alps, the Alpenverein was able to support the Austrian army in its war in the mountains. All in all, however, it may be said without exaggeration that the Deutsche und Österreichische Alpenverein contributed a great deal and substantially to the exploration, the knowledge and - by making them more easily accessible - the popularity of the Alps, to the expansion of the members horizons and perceptions as well as, finally, to the material and in many cases spiritual improvement of the alpine regions themselves.